Vázquez Cano, Esteban; López Meneses, Eloy; BARROSO OSUNA, Julio (2015). El Futuro de los MOOC. Retos de la formación on line, masiva y abierta. Madrid: Editorial Síntesis - Sintes Rodrigo, Pedro Manuel (Revista Fuentes, 2015)
VÁZQUEZ CANO, Esteban; LÓPEZ MENESES, Eloy; BARROSO OSUNA, Julio (2015). El Futuro de los MOOC. Retos de la formación on line, masiva y abierta. Madrid: Editorial Síntesis